Um modelo explicativo do avanço na qualidade da educação do ensino fundamental no estado do Ceará - Verdiano, Aurilano de Araújo (2019)
In the last few years, the state of Ceará has shown improvements in the results in basic education when it comes to the public sector, especially in the initial years of Elementary School. The present study aims to show a quantitative analysis of the data produced by the Basic Education Assessment System (SAEB), as well as in the qualitative analysis, through what researchers say about both current and past scenarios of Brazilian education, for an eval- uation of possible explanations on quality evolution of municipal public education in the State of Ceará. The different Education definitions work together for the common notion of a hu- man ideal as a general aim. For so, nowadays, learning to read, write, and rationalize in a log- ical-mathematical way is essential and occur, for most children in public schools today. The information age and globalization have brought challenges to formal school education in face of human social diversities such as the student's necessity of thinking about the reality around them and their needs to communicate with their peers. The law that regulates education in Brazil (LDB) provides us with the means to overcome such challenges, one of which is the basic principle for guaranteeing the quality standard of education. Education quality involves many variables and can be restrictedly measured through large-scale assessments. The SAEB consists of a set of external evaluations in a large scale, which allows the procedure of basic education diagnosis, providing an indication of the education quality offered. In search for explananing the proficiency growth in the State of Ceará in the SAEB, we used different ana- lyzes of the results published by the National Institute of Educational Studies and Research Anísio Teixeira (INEP) from 2005 to 2017 and the 2017 microdata were used as well. Based on such analyzes, there was a monotonical increase on the level of the municipal average marks over the years, reaching and consolidating values which are compatible with situations of much more developed regions such as the South and Southeast, whose explanation differs from those traditionally given. The interpretation of the results points to a factor whose mo- ment of time coincides with that in which the state management began to guide and support the municipalities of Ceará, incorporated through the Literacy Program in the Right Age (PAIC). In addition, the adopted management model is about to reach its limit, suggesting re- inforcement in the current model: the emphasis on the professional valorization of teachers.